1993
DOI: 10.1128/aac.37.3.512
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of granulocyte-macrophage colony-stimulating factor and zidovudine in patients with AIDS and severe AIDS-related complex

Abstract: Granulocytopenia is a complication of human immunodeficiency virus disease, as well as a toxic manifestation of zidovudine therapy. To evaluate pharmacokinetic and pharmacodynamic relationships, 11 AIDS-AIDSrelated complex patients who had developed zidovudine-associated granulocytopenia (mean absolute neutrophil count, 1,077/mm3) were examined after addition of granulocyte-macrophage colony-stimulating factor (GM-CSF) to zidovudine. GM-CSF was administered as a daily (1.0 or 0.3 pg/kg) or every-other-day (0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…Furthermore, the murine model is characterized by genetic uniformity that minimizes differences in serum GM-CSF levels within each group. In contrast, humans who received the same recombinant GM-CSF dose demonstrate significant differences in peak serum concentrations (38). For this reason, it is difficult to identify a precise dose of GM-CSF to be used in a vaccine formulation.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, the murine model is characterized by genetic uniformity that minimizes differences in serum GM-CSF levels within each group. In contrast, humans who received the same recombinant GM-CSF dose demonstrate significant differences in peak serum concentrations (38). For this reason, it is difficult to identify a precise dose of GM-CSF to be used in a vaccine formulation.…”
Section: Discussionmentioning
confidence: 87%
“…GM-CSF, an important growth factor for hematopoietic cells, is released mainly from T cells and is involved in stimulating neutrophil, monocyte, macrophage and eosinophil colony formation [30,31]. GM-CSF has been clinically used as an anti-HIV drug regimen to reduce hematopoietic cell death caused by drug therapy [32]. A number of studies have reported enhancement of cellular or humoral responses from cytokine codelivery [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that GM-CSF activation of monocytes increases the resistance of these cells to HIV by both impairing viral entry and enhancing the activity of some antiretroviral agents [5][6][7][8][9]. Preliminary clinical trials have supported these findings, demonstrating reductions in virus load in some individuals receiving GM-CSF therapy [10,11]. Therefore, GM-CSF therapy was evaluated to maintain or improve host defenses in HIV-infected individuals.…”
mentioning
confidence: 98%